Descripción de métodos preventivos y de control de nemátodos gastrointestinales en caninos. - Litardo Cabrera, José Francisco (2022)
Parasitic infections in canines have a worldwide distribution and are characterized by nonspecific intestinal symptoms; by clinical processes that can be acute, subacute and chronic. The epidemiology of intestinal parasites is very varied. These represent a threat to domestic animals, since they cause anorexia, reduced food intake, loss of blood and plasmatic proteins in the gastrointestinal tract, alterations in protein metabolism, reduction of minerals, depression in the activity of some intestinal enzymes and diarrhea. Toxocariasis, produced mainly by the nematode Toxocara canis and to a lesser extent by Toxocara cati, is a parasitic zoonosis that is easily acquired. Another of the gastrointestinal parasites is Ancylostoma caninum, which is a species of nematode that mainly infects the small intestine of dogs. The infection varies from asymptomatic cases to the death of the animal. Infestation by soil-transmitted nematodes has increased and has been recognized as an important public health problem, particularly in developing countries. Dogs carry a variety of parasites in the gastrointestinal tract made up of nematodes, trematodes and cestodes, which makes them definitive hosts of some species of zoonotic parasites. In the present investigation, the Qualitative and Exploratory method was used based on data from scientific journals, web pages, pharmacology books, information obtained from academic Google bibliographies and scientific articles.